A new species of Cnemidophorus (Squamata, Teiidae) from the South American Chaco - Cabrera, Mario Roberto (2012)
Comprising one million of square kilometres, the Chaco biome is one of the largest open formations of South America, and part of a biogeographic diagonal in loose continuity with the Cerrado, to north, and the Patagonian Monte to south. Until recent years only one species of Cnemidophorus of the ocellifer group was recognized, C. ocellifer (Spix), but in the last decade several new species from the group has been described to Caatingas and Cerrado. In this paper a new species of Cnemidophorus in the ocellifer group, previously regarded as the southernmost population of  C. ocellifer, is described. Analyses of external morphology revealed  that a number of traits known to be taxonomically informative differ from trait combinations known to other species of the genus. The new species is bisexual, and distinguished from all other taxa of Cnemidophorus by its own combination of character states: it has 75-98 granular dorsal scales across midbody; 184-212 dorsal scales along vertebral line; 15-19 femoral pores in total; 25-31 lamellae under fourth toe; two rows of enlarged prebrachial plates; two rows of scales along the inferoposterior half of the calf of males bearing erected thorn-like borders; 23-26 scales around the tail on the fifth complete postcloacal ring; 5 superciliaries; frontonasal scale subrhombical, wider than long; striped pattern on body and tail with unfading of white stripes in adults, and vertebral stripe absent. The range of the new species in Paraguay and Argentina strongly suggests it is endemic to the Chaco biome. Its presence in the near Bolivian Chaco is expected.